Punishment, participatory democracy, and the jury - Dzur, Albert W. (New York ; Oxford : Oxford University Press, 2012)
Focusing contemporary democratic theory on the neglected topic of punishment, this book argues for increased civic engagement in criminal justice as an antidote to the American penal state. It considers how the jury may serve as a participatory institution that gathers and utilizes citizen's juridical capabilities rather than merely expressing unreflective public opinion.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Aug. 24, 2012).
Keywords: Jury -- United States; Punishment -- United States; Democracy -- United States; Political participation -- United States